دراسة 25 حالة سرطان الشائك الخلايا في الشفة السفلية - وهبة عيسى; قسومة جمال; قباني نبيلة نعمان (Latakia University Journal -Medical Sciences Series, 2019)
المقدمة: يُعدّ سرطان الشفة السفلية الشائك الخلايا واحداً من أكثر أنواع سرطانات الفم شيوعاً. على الرغم من أن هذا النوع من السرطانات قابل للعلاج بسهولة عادة مقارنة بخباثات مواقع فموية أخرى ولكن يمكن أيضاً أن يحدث بسبب هذا المرض نقائل ناحية ونكس موضعي أو الموت. الهدف من الدراسة: هدفت هذه الدراسة إلى تحديد نسبة حصول النقائل العقدية اللمفية ومستويات الانتقالات العقدية اللمفية الأكثر إصابة والعلاقة بين العمر ومستويات الانتقالات العقدية اللمفية. المواد والطرائق: تضمنت الدراسة /25/ مريضاً مصاباً بالـ SCC الأولي على الشفة السفلية ممن عولجوا في مشفى المواساة وذلك بهدف التدبير الشفائي. خضع كل المرضى للاستئصال الجراحي للورم مع ترك هوامش جراحية لا تقل عن 5مم إضافة إلى تجريف العنق تبعاً للاستطباب. النتائج: صنف72% من المرضى على أنهم N0 ووجدت النقائل العقدية عند 20% على هيئة N1 و8% على هيئة N2a. عانى 16% من المرضى من نقائل رقبية إلى المستوى Ia و 8% منهم إلى المستوى Ia+Ib في حين أنه فقط 4% من المرضى لديهم انتقال إلى المستوى II. العلاقة بين العمر ومستوى العقد اللمفية في العنق لم تظهر فروقات ذات دلالة إحصائية. الخلاصة: خلصت هذه الدراسة إلى شيوع إصابة السرطان الشائك الخلايا في الشفة السفلية عند الذكور مقارنة بالإناث وخصوصاً في العقد السابع من العمر وأن المستوى الأول (لاسيما المنطقة تحت الذقنية) هي الأكثر تأثراً بالانتقالات العقدية مع عدم وجود علاقة بين المستوى المصاب والعمر. Introduction: Lower lip squamous cell carcinoma is one of the most common types of cancers of the oral cavity. Although it is generally readily curable compared with malignancies at other oral sites, regional metastasis, local recurrence and even death from this disease may occasionally occur. Aim of Study: The study aimed to determine The ratio of cervical node metastasis, the most affected levels of lymph node metastasis, and the correlation between age and levels of lymph node metastasis. Materials &Methods: The study included 25 patients with primary lower lip SCC, treated in Al Moasat hospital for the curative management. All patients underwent surgical resection of the tumor with surgical margins not less than 5 mm as well as neck dissection according to the indication. Results: 72% of patients were classified as N0. Nodal metastasis was present in 20% as N1 and 8% as N2a and 16% of patients suffered from cervical metastasis to the level /Ia/, 8% to /Ia +Ib/ and 4% to the level /II/. The correlation between age and level of lymphatic node did not reveal statistically significant differences. Conclusion: This study concluded that squamous cell carcinoma of the lower lip is more common in males than in females particularly in the 7th decade of age, and Level I (especially for the submental area) is the most affected by nodal metastases with no correlation in between the affected level and the age.